2017
DOI: 10.1002/2017gl073582
|View full text |Cite
|
Sign up to set email alerts
|

Long‐period long‐duration seismic events during hydraulic fracturing: Implications for tensile fracture development

Abstract: Long‐period long‐duration (LPLD) seismic events are observed from a microseismic data set acquired by surface receivers in the Eagle Ford Shale. These events are characterized by low frequencies of 10–60 Hz and long durations of 30–60 s. The seismograms are dominated with P waves, and the frequency spectra have peaks at several isolated frequencies, similar to volcanic tremors. The LPLD events are located close to the horizontal hydraulic treatment well and migrate away from the well with time. These observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 32 publications
(65 reference statements)
0
11
2
Order By: Relevance
“…For example, the duration of our detected LPLD events is more than 300 s, much longer than the typical duration of 30-60 s for the LPLDs in the other studies. Furthermore, whereas the dominant frequency of our LPLD events is less than 10 Hz, the LPLD events during hydraulic fracturing can reach up to 60-100 Hz (Das and Zoback, 2013a,b;Hu et al, 2017;Chen et al, 2018). These differences suggest that the source mechanisms of LPLD events observed in this study are different from recent observations near hydraulic fracturing sites.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…For example, the duration of our detected LPLD events is more than 300 s, much longer than the typical duration of 30-60 s for the LPLDs in the other studies. Furthermore, whereas the dominant frequency of our LPLD events is less than 10 Hz, the LPLD events during hydraulic fracturing can reach up to 60-100 Hz (Das and Zoback, 2013a,b;Hu et al, 2017;Chen et al, 2018). These differences suggest that the source mechanisms of LPLD events observed in this study are different from recent observations near hydraulic fracturing sites.…”
Section: Discussioncontrasting
confidence: 77%
“…Recent studies have shown that hydraulic-fracture operations could induce LPLD tremor-like events (Das and Zoback, 2013a,b;Hu et al, 2017). Although some LPLD events in their studies might be small regional earthquakes (Caffagni et al, 2015;Chen et al, 2018), the characteristics of the LPLD events observed in this study are different from any of them.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, during hydraulic fracturing of shale reservoirs, the moment released by microearthquakes within the stimulated rock volume is much smaller than theoretical prediction based on the amount of fluid injected in the formation, revealing an energy deficit (e.g., Das & Zoback, 2013;Goodfellow et al, 2015;Kumar et al, 2017;Warpinski et al, 2012). Recently, it has been shown that this energy deficit is related with other deformation mechanisms associated with slow but accelerated shear slip along preexisting faults (Boroumand & Eaton, 2012;Caffagni et al, 2016;Das & Zoback, 2013;Eaton et al, 2013;Hu et al, 2017;Kumar et al, 2017;McGarr & Barbour, 2018;Zecevic et al, 2016). In addition, long-period long-duration (LPLD) events are commonly observed during the hydraulic stimulation of shale reservoirs and they have similar characteristics as tectonic tremors observed during slow-slip events at the plate boundary (Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%